ANALYSIS OF THE LEVEL OF UNDERSTANDING OF RURAL COMMUNITIES ON THE BENEFITS OF SHARIA INSURANCE PRODUCTS IN INDONESIA - Padlan Habibi; Nurul Jannah; Atika (SOSIOEDUKASI, 2025)
This study aims to examine the extent of rural people's understanding of the benefits of sharia insurance products, especially in East Sidorame Village, Medan Perjuangan District. This study uses a quantitative approach with a survey method involving respondents from the local community. The results of this study show that people's understanding of sharia insurance is quite diverse, with several factors such as education level, sources of information, and previous experience affecting their perception of the product. These findings provide an important picture for sharia insurance providers and policymakers in developing more effective socialization strategies to increase awareness and utilization of sharia insurance products in rural communities. Thus, this researcher helps strengthen the role of sharia insurance as a financial protection solution in accordance with sharia principles in rural communities.